Prevalência da infecção por enteroparasitas e sua relação com as condições socioeconômicas e ambientais em comunidades extrativistas do município de Cairu - Bahia (D.O.I.: 10.5216/reec.v7i2.27445) - Cunha, Gabriel Muricy; Moraes, Luiz Roberto Santos; Lima, Artur Gomes Dias; Matto, Paulo Sérgio de Morais da Silveira; Frediani, Daniel Augusto (REEC - Revista Eletrônica de Engenharia Civil, 2013)
RESUMO: As parasitoses intestinais mantêm-se como um dos maiores problemas de saúde pública em áreas rurais do Norte e Nordeste do Brasil. A pesquisa teve como objetivo realizar o inquérito da prevalência de enteroparasitas em comunidades extrativistas do município de Cairu-BA que possuíam diferenças marcantes no acesso aos serviços públicos de saneamento básico. Por meio de estudo de corte transversal com emprego do método de sedimentação espontânea foram examinados 311 indivíduos de diferentes faixas etárias. Foram levantadas informações sobre os aspectos socioeconômicos e ambientais por meio da aplicação de questionário pré-codificado padrão. Foi utilizado o software Statistical Package for Social Sciences (SPSS) para análise dos dados coletados. Na localidade de Garapuá, 74,7% dos indivíduos examinados estavam parasitados e 30,8% estavam poliparasitados. As espécies enteroparasitas mais prevalentes foram: Endolimax nana (54,1%), Giardia lamblia (29,5%), Trichuris trichiura (28,1%) e Entamoeba histolytica (21,2%). Na localidade de Monte Alegre, 98,2% dos indivíduos estavam parasitados e 74,8% estavam poliparasitados. As espécies enteroparasitas mais prevalentes foram: Endolimax nana (88,3%), Entamoeba histolytica (64,0%), Ancylostoma sp. (55,9%) e Entamoeba coli (51,4%). Na localidade da Batateira, 96,3% dos indivíduos examinados estavam parasitados e 79,6% (43/54) estavam poliparasitados. As espécies enteroparasitas mais prevalentes foram: Endolimax nana (87,0%), Trichuris trichiura (68,5%), Entamoeba histolytica (66,7%) e Ascaris lumbricoides (46,3%).ABSTRACT: Intestinal parasitic diseases remain one of the major public health problems in rural areas of the North and Northeast of Brazil. This research aimed to survey the prevalence of intestinal parasites in extractive communities in the city of Cairu - BA which had marked differences in access to basic sanitation public services. The survey of the prevalence of intestinal parasites and survey data on the socioeconomic and environmental aspects were performed by means of cross-sectional study. The Socioeconomic and environmental aspects was conducted through interviews at the household level, with the use of standard questionnaire semi-structured and pre-coded. The qualitative fecal examinations were performed by the technique of spontaneous sedimentation. The study population was composed of individuals of all ages residing in the village of Monte Alegre and Batateira, and children (0-14 years) living in the village of Garapuá. Examined a total of 311 individuals. The results were described with the use of the Statistical Package for Social Sciences. In the village of Garapuá, 74,7% of the individuals examined were parasitized and 30.8% were infected of three or more intestinal parasites. The species most prevalent were Endolimax nana (54,1%), Giardia lamblia (29,5%), Trichuris trichiura (28,1%) and Entamoeba histolytica (21,2%). In the village of Monte Alegre, 98,2% of individuals were infected and 74,8% were infected of three or more intestinal parasites. The species most prevalent were Endolimax nana (88,3%), Entamoeba histolytica (64,0%), Ancylostoma sp. (55,9%) and Entamoeba coli (51,4%). In the village of Batateira, 96,3% of the individuals examined were infected and 79.6% (43/54) were infected of three or more intestinal parasites. The species most prevalent were Endolimax nana (87,0%), Trichuris trichiura (68,5%), Entamoeba histolytica (66,7%) and Ascaris lumbricoides (46,3%).